A motion area in human visual cortex. - Orban, G A (1995)
We have localized an area in the human brain involved in the processing of contours defined by motion differences (kinetic contours) by comparing with positron emission tomography the regional cerebral blood flow in tasks performed with kinetic and luminance-defined gratings. These tasks included passive viewing, counting the total number of grating stimuli, and counting the number of gratings of a given orientation. Comparison between the counting tasks and passive viewing with a given type of contour revealed a set of active areas that were similar for both luminance-defined and kinetic contours. Comparisons between these two types of contours revealed a single focus in the right hemisphere that did not overlap with the many regions activated by uniform motion. In particular this "kinetic focus" was clearly separated from the area previously defined as the human homologue of V5/middle temporal. Activity in this kinetic focus was stronger when orientation had to be processed than in the other two tasks. These results and control experiments with uniformly moving random dot patterns suggest the existence of an area in the human visual system that is activated much more by kinetic contours than by luminance contours or uniformly moving random dots. Up to now, such an area has not been described in the monkey visual system.